Effects of dietary aspirin supplementation on liver enzymes, immune response, cecum microflora and fatty acids profile in breast meat of broiler chickens - Tavakoli, M; Bouyeh, M; Seidavi, A (Journal of the Hellenic Veterinary Medical Society, 2022)
The present study was performed to investigate the effect of dietary aspirin (A) on broilers. A completely randomized design using 120 one-day-old male broiler chicks Ross 308, three levels of aspirin (0, 50, and 100 mg/kg) was used in 4 replicates, each including 10 chicks, during 42 days. The effects of different levels of aspirin, added to a basal diet, on blood plasma parameters, liver enzymes, immune system, cecal microflora, and fatty acids profile of breast muscle of chicks were investigated. Data analysis was performed by SAS statistical software and the comparison of the means with Duncan's test. The results showed that the effects of aspirin on blood parameters, liver enzymes of broilers (except for alkaline phosphatase which significantly reduced), the humoral immune system in response to antigen injection as sheep red blood cell (SRBC), antibody titer against Newcastle and influenza virus were not significant (P≥0.05). The highest percentage of neutrophils and eosinophils was related to this treatment. Also, aspirin treatments increased numerically the levels of unsaturated fatty acids and decreased saturated fatty acids. Moreover, aspirin led to a reduction in the population of Escherichia coli. So, based on the results of the present study, the use of 100 mg/kg aspirin in the diet of broilers is recommendable.